THE RELATIONSHIP OF ARM MUSCLE EXPLOSION AND WASTE MUSCLE FLEXIBILITY TOWARDS SMASH ABILITY OF BOLAVOLILE ATHLETES - simatupang, antonius togu; Sin, Tjung Hauw; M., Masrun; Sari, Desi Purnama (Jurnal Gladiator, 2022)
The problem in this study is that the accuracy of the smash of volleyball athletes at SMAN 12 Padang. The variables of this study are the explosive power of the arm muscles (X1) and waist flexibility (X2) and smash ability (Y). (X1) and waist flexibility (X2) and smash ability (Y). This study aims to determine how big the relationship between arm muscle explosive power. and waist flexibility on the smash ability of extracurricular volleyball athletes at SMA 12 Padang. This type of research is correlational. The population of this study was all volleyball athletes at SMA Negeri 12 Padang. The population of this study was all volleyball athletes from extracurricular 12 Padang students totaling 25 people. male volleyball 15 people. While the total sampling is sampling. The instrument used in this study is the arm muscle explosive power test with one hand medicine ball put test, flexibility with flexsiometer test and smash ability test. Data analysis technique with product moment correlation and multiple correlations. The results of the analysis show: 1) There is a significant relationship between arm muscle explosive power and smash accuracy, which is significant thit (3.21) > ttab (1.77) with a contribution of 0.665%. 2) There is a significant relationship between waist muscle flexibility and smash accuracy, which is stated to be significant thit (2.76) > ttab (1.77) with a contribution of 0.608%. 3) There is a relationship between explosive power of arm muscles and flexibility of waist muscles together with smash accuracy which is stated to be significant Fcount (7.79) > Ftable (3.74) with a contribution of 0.752%.